PENGARUH PERSEPSI RISIKO, VARIASI, KUALITAS DAN HARGA PRODUK TERHADAP SIKAP KONSUMEN - Febrian Humaidi Sukmana (Valid: Jurnal Ilmiah, 2018)
The phenomena of the used clothes trade nowadays are getting more attracting. Proven by the increasing number of spots offering various kinds of used clothes, one of it is Karang Sukun used clothes market, located in the heart of Mataram city. The aim of this research is to find out the influence of customer perception related to risk, variation, quality and price of the product toward the preference of used clothes customer. To be more specific, there are four hypotheses aimed to be proven through quantitative approach. Analysis method applied in this research is double linear regression (using SPSS 16.0 for windows as data managing tool). According to data analysis result, it concluded that: first, customer perception variables that consist of perception on risk, product variation, quality and price of the product are equally (simultaneously) influencing the preference of used clothes customer. Second, partially (each free variable/ customer perception) as proposed in hypothesis formulation, provides evidence that the hypothesis are supported by managed and analyzed data, in other words, all of the formatted hypothesis in this research is statistically unrejectable. Third, customer perception on quality of the product is dominantly influencing the preference of used clothes customer.